2022
DOI: 10.3389/fimmu.2022.817829
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Treatment in Patients with Covid-19: A Systematic Review and Meta-Analysis

Abstract: Convalescent plasma is a suggested treatment for Coronavirus disease 2019 (Covid-19), but its efficacy is uncertain. We aimed to evaluate whether the use of convalescent plasma is associated with improved clinical outcomes in patients with Covid-19.In this systematic review and meta-analysis, we searched randomized controlled trials investigating the use of convalescent plasma in patients with Covid-19 in Medline, Embase, Web of Science, Cochrane Library, and medRxiv from inception to October 17th, 2021. Two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
(86 reference statements)
1
34
0
2
Order By: Relevance
“…Coinciding with other studies, HP was a safe therapy [ 11 , 18 , 19 , 20 ], and no differences were found in other endpoints [ 19 , 21 , 22 ]. Our results are in line with the information summarized by Jorda et al [ 23 ]—sixteen clinical trials focused on the use of plasma for the treatment of COVID-19. The clinical improvement was analyzed in four out of the sixteen trials, varying the definition of clinical improvement among them and without consensus on the results; therefore, the hypothesis of an effect on the time of clinical improvement was downgraded due to concerns regarding the risk of bias or incomplete sample recruitment, as is the case with this trial.…”
Section: Discussionsupporting
confidence: 92%
“…Coinciding with other studies, HP was a safe therapy [ 11 , 18 , 19 , 20 ], and no differences were found in other endpoints [ 19 , 21 , 22 ]. Our results are in line with the information summarized by Jorda et al [ 23 ]—sixteen clinical trials focused on the use of plasma for the treatment of COVID-19. The clinical improvement was analyzed in four out of the sixteen trials, varying the definition of clinical improvement among them and without consensus on the results; therefore, the hypothesis of an effect on the time of clinical improvement was downgraded due to concerns regarding the risk of bias or incomplete sample recruitment, as is the case with this trial.…”
Section: Discussionsupporting
confidence: 92%
“…We primarily stratified our analyses by type of population: hospitalized and non-hospitalized COVID-19 patients, and high risk of COVID-19 infection (prophylaxis). We performed random effects meta-analyses using the inverse variance method, the Paule-Mandel method to calculate the between study variance tau 2 , and the Hartnung-Knapp method to adjust 95% confidence intervals (CIs) 8 , 9 . Effects were reported as relative risks (RR) with their 95%CIs for dichotomous outcomes and mean differences (MD) with their 95%CIs for continuous outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Several therapies have received emergency use authorization to prevent hospitalizations or death in COVID-19 patients or to prevent high risk people from becoming infected by SARS-CoV-2. Convalescent plasma, a therapy based on neutralizing SARS-CoV-2 virus with a previously infected person's antibodies, was given emergency authorization; however, it did not demonstrate significant clinical benefits in systematic reviews 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The selection and definition of outcomes referred to the previous meta-analysis ( 8 , 12 ) and RCTs. The primary outcome was the 28-d mortality.…”
Section: Methodsmentioning
confidence: 99%